Child training in Supowmu-1 - Nicholas, T.A (University of Ghana, 1957)
Supowmu Dunkwa is on the cape coast-secondi road chiefly in these modern days by motor vehicular conveyance one come upon a cluster of sun –baked mud wall buildings stretching fairly parallel to the motor road for about two hundred yards and about the same number of yards deep towards the left.Suddenly because of a sharp bend of the road less than 300 yards from it and because of the thick forest which half conceals it
Keywords: Training; Child; Inhabitants; Supowmu-Dunkwa